2023
DOI: 10.25271/sjuoz.2023.11.1.1041
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Methicillin-Resistant Staphylococcus Aureus (MRSA) Recovered from Patients with Urinary Tract Infections in Zakho City/ Kurdistan-Iraq

Abstract: The prevalence of Staphylococcus aureus (S. aureus) among patients with urinary tract infections (UTIs)  has become a significant cause of morbidity in all age groups. The aim of the current study  was to identify S. aureus with methicillin-resistant S. aureus (MRSA). Moreover, it aimed to determine their antimicrobial susceptibility patterns and to detect the presence of the mecA, lukPV and icaA genes in isolated S. aureus among UTIs patients. A total of 402 urine samples were collected from patients diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Overall, among the 310 hospitalized patients tested for the presence of Staphylococcus aureus, the prevalence of this bacterium were 10.64%, of which 51.5% were found to be MRSA. This prevalence rate of S. aureus was relatively comparable with that reported by Hami and Ibrahim (2023) who reported 12.6% of this bacterium in clinical samples (urine). Also, the prevalence rate of MRSA was in line with that obtained by Hussein et al, (2019), who reported the prevalence rate of 50.4% of MRSA among the Hospital Staff.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, among the 310 hospitalized patients tested for the presence of Staphylococcus aureus, the prevalence of this bacterium were 10.64%, of which 51.5% were found to be MRSA. This prevalence rate of S. aureus was relatively comparable with that reported by Hami and Ibrahim (2023) who reported 12.6% of this bacterium in clinical samples (urine). Also, the prevalence rate of MRSA was in line with that obtained by Hussein et al, (2019), who reported the prevalence rate of 50.4% of MRSA among the Hospital Staff.…”
Section: Discussionsupporting
confidence: 89%
“…Also, the prevalence rate of MRSA was in line with that obtained by Hussein et al, (2019), who reported the prevalence rate of 50.4% of MRSA among the Hospital Staff. However, Hami and Ibrahim (2023) found a much higher prevalence rate of MRSA (75.7%) in Zakho General Hospital. In contrast, the prevalence of MRSA in the present study was almost tripled than that reported by Yassin, (2022) in a cross-sectional study conducted in Duhok city, who reported 18% of MRSA among medical college students.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly , another study depicted that approximately 53% of E. coli isolates from UTIs in Duhok city were resistant to Ciprofloxacin and levofloxacin (Hussein et al, 2017). Furthermore, many other studies conducted in Kurdistan Region showed variation in the percentages of resistance against members of fluoroquinolones antibiotics from both gram positive and negative bacteria isolated from UTIs (Hasan et al, 2022;Hami et al, 2023). This increase in the trend of resistance for the FQ antibiotics might be due to the overuse and abuse of these antibiotics.…”
Section: Discussionmentioning
confidence: 95%
“…The excessive and improper use of antibiotics, particularly broad-spectrum antibiotics, plays a major role in the emergence of drug-resistant strains, as observed in several studies ( Doern et al, 2014 ; Tessema et al, 2021 ; Hasan and Ibrahim, 2022 ; Hami and Ibrahim, 2023 ; Ibrahim, 2023 ). Neonatal sepsis caused by antimicrobial-resistant (AMR) bacteria is a multifactorial issue of global concern due to the increased illness, death, and hospital expenses associated with it.…”
Section: Introductionmentioning
confidence: 99%